Uji Toksisitas Bahan Aktif Niklosamida Terhadap Crustacea Sebagai Water Treatment dalam Budidaya Udang Vannamei (Litopenaus vannamei) - Aan Fahrizki; Herman Yulianto Yulianto; Asep saefulloh (Politeknik Negeri Lampung., 2015)
This study aims to determine the level of toxicity of the active ingredient based niclosamide on the value LC50- 24h against crustaceans and the duration of the residual effect of niclosamide in water. Methods This study used a completely randomized design with 4 different concentration levels and 0 ppm as a control. Toxicity tests using a concentration of 1.7783; 3.1623; 5.6235 and 10.0002 ppm. To determine the duration of the test using the residual effects of detoxification. In the detoxification test stick with a concentration in the toxicity test. Probit analysis results in test animals showed values (LC50) - 24 hours amounted to 3.6282 ppm, while the length of the residual effects of niclosamide in water for 96 hours. Kata kunci : Crustacea, niclosamide, and toxicity